Effect of integrated perioperative rehabilitation intervention under the fast-track surgery concept on stress and complications in patients undergoing craniocerebral injury surgery - Zhao, Bin; Wang, Heng (Frontiers in Surgery, 2023)
Objective To observe the intervention effect of perioperative rehabilitation intervention of integrated medical care the concept of FTS on stress response and postoperative complications in patients undergoing craniocerebral injury surgery. Methods 70 patients with Traumatic brain injury (TBI) admitted to the Department of Neurosurgery of our Hospital from January 2019 to December 2021 were as the research objects and were divided into general group and FTS group according to the random number table method, with 35 cases in each group. The general group was intervened with perioperative basic nursing measures for TBI, and the FTS group was intervened with perioperative rehabilitation model of integrated medical care under the concept of FTS on the basis of the general group. The two groups of patients were compared in hemodynamic indexes (heart rate, mean arterial pressure), stress hormone levels (CORT, GLU, E), changes in motor neurological function (GCS score, NHISS score, FMA score), occurrence of postoperative complications (infection, pressure sores, rebleeding, central hyperthermia), short-term quality of life (SF-36) before and after the intervention. Results After intervention, the levels of HR, MAP, COR, GLU, and E were significantly lower in FTS group than in the general group (all P < 0.05). After intervention, the Fugl-Meyer score and Barthel index score of upper and lower extremities in both groups were significantly higher than those before intervention, and the FTS group was higher than the general group, and the difference was statistically significant (P < 0.05). After the intervention, the NIHSS scores were significantly lower in both groups than before the intervention, and the FTS group was lower than the general group, and the differences were statistically significant (P < 0.05). Short-term physical function, somatic pain, physical function, general health status, social function, energy, mental health, and emotional function scores were significantly higher in the FTS group than in thegeneral group, and all differences were statistically significant (P < 0.05). The total incidence of infection, pressure ulcers, rebleeding, central high fever and other complications in the FTS group was significantly lower than that in the general group (P < 0.05). Conclusion The implementation of integrated perioperative rehabilitation interventions under the concept of FTS for patients with TBI can significantly alleviate patients’ stress, promote recovery, reduce the incidence of complications, and improve short-term quality of life, which is worthy of clinical promotion.